(3EYGOI gjcdI hNUNUI GdeDSSGJ GdeGdjIs - (3eMeO(B, (3eMehO jhSas ((3GdbGgQI(B:s (3GdefXeI GdYQHjI ddJfejI GdGOGQjI(B,s, 2007)
(3gjcd GdShb GdeUQj ddNOeGJ GdeGdjI, HQfGeL GdNUNUI hGYGOI GdgjcdI dbWGY GdJCejf, HQfGeL GdNUNUI hGYGOI gjcdI GdbWGY GdeUQaj, GdGbJUGO Gdcdj hGdJYOjdGJ GdJTQjYjI PGJ GdJCKjQ, JfejI Shb GdJCejf GdeUQj JhbYGJ NOeGJ GdJCejf OGNd GdShb GdeUQj, GSJQGJjLjI GdGSJMhGP Ch GdGfOeGL dRjGOI GdbGYOI GdQCSeGdjI hCgejI Pdc aj bWGY GdNOeGJ GdeGdjIs
(3HHdjhZQGajG(B: (3U(B.195(3; edGMb U(B.201s
Keywords: (3GdJCejf (B- (3GdHfhcs; (3GdNOeGJ GdeUQajIs; (3GdQCSeGdjIs